Altered Airway Microbiota Composition in Patients With Pulmonary Hypertension. Issue 5 (November 2020) - Zhang, Chenting; Zhang, Tingting; Lu, Wenju; Duan, Xin; Luo, Xiaoyun; Liu, Shiyun; Chen, Yuqin; Li, Yi; Chen, Jiyuan; Liao, Jing; Zhou, Dansha; Chen, Xu; et al.
Abstract : Alteration in microbiota composition of respiratory tract has been reported in the progression of many chronic lung diseases, yet, the correlation and causal link between respiratory tract microbiota and the disease development of pulmonary hypertension (PH) remain largely unknown. This study aims to define and compare the respiratory microbiota composition in pharyngeal swab samples between patients with PH and reference subjects. A total of 118 patients with PH and 79 reference subjects were recruited, and the pharyngeal swab samples were collected to sequence the 16S ribosomal RNA (16S rRNA) V3-V4 region of respiratory microbiome. The relative abundances in patients with PH were profoundly different from reference subjects. The Ace and Sobs indexes indicated that the microbiota richness of pharynx value is significantly higher; while the community diversity value is markedly lower in patients with PH, comparing to those of the reference subjects. The microbiota on pharynx showed a different profile between the 2 groups by principal component analysis. The linear discriminant analysis effect size also revealed a significantly higher proportion of Streptococcus, Lautropia, and Ralstonia in patients with PH than reference subjects. The linear discriminant analysis effect size output, which represents the microbial gene functions, suggest genes related to bacterial invasion of epithelial cells, bacterial toxins were enhanced, while genes related to energy metabolism, protein digestion and absorption, and cell division pathways were attenuated in patients with PH versus reference subjects. In summary, our study reports the first systematic definition and divergent profile of the upper respiratory tract microbiota between patients with PH and reference subjects. Abstract : Supplemental Digital Content is available in the text.